1990
DOI: 10.1097/00006123-199010000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological experience with pineocytomas

Abstract: The clinicopathological experience associated with five cases of pineocytoma is presented. All patients were treated by surgical removal without postoperative radiotherapy. In three individuals, 2000 cGy was administered to the tumor as a presurgical diagnostic test, with no evidence of response. All cases demonstrated histological features of pineocytoma, according to the criteria of Borit et al., and of the so-called "pineocytoma with neuronal differentiation," according to the criteria of Rubinstein. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Tumor size decreases by up to 70% and even complete regressions have been described [14] as well as excellent local tumor control rates of up to 100% for small tumors [10]. In an older analysis with only five patients, Vaquero et al [15] showed that postoperative radiation after surgical removal can be omitted, even in case of local invasion in PPTs with neuronal differentiation. Especially in older studies, pineocytomas, however, did sometimes not behave as benign as expected, particularly in younger patients [16-18].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size decreases by up to 70% and even complete regressions have been described [14] as well as excellent local tumor control rates of up to 100% for small tumors [10]. In an older analysis with only five patients, Vaquero et al [15] showed that postoperative radiation after surgical removal can be omitted, even in case of local invasion in PPTs with neuronal differentiation. Especially in older studies, pineocytomas, however, did sometimes not behave as benign as expected, particularly in younger patients [16-18].…”
Section: Discussionmentioning
confidence: 99%
“…1 Five-year survival rates after tumor subtotal resection with or without RT is around 80%; there was no statistically significant difference in overall survival among patients with or without post-operative radiation. 1,3,15,21,24,27,29,31,34,41,47,51,52 In the pre-microneurosurgical era, mortality rates after surgery for pineal region and posterior third ventricle tumours was high, between 50% and 70%, probably because of the critical location adjacent to the midbrain and the deep cerebral veins. 54,[67][68][69][70][71] Microsurgical techniques have significantly reduced mortality rates to about 2%.…”
Section: Discussionmentioning
confidence: 99%